Underreporting of molecular targets in surgically treated patients with peritoneal metastasis of gastric cancer - Castagna, Arianna; Ramouz, Ali; Trinidad-Gutiérrez, I.; Brindl, Niall; Brandl, Andreas (European journal of surgical oncology, 2025)
The management of gastric cancer (GC) with peritoneal metastasis (PM) remains a significant clinical challenge. Despite advances in molecular profiling, the underreporting of key molecular markers in patients undergoing surgical treatment for GC with PM is concerning. Signet ring cell (SRC) histology is associated with poor prognosis and chemoresistance, while Laurén diffuse subtype is linked to a higher risk for PM. Despite the established role of HER2 in GC progression, its impact on the efficacy of surgical treatment is not clearly defined. The lack of comprehensive reporting on these and recent molecular markers underscores the need for further research. Incorporating molecular diagnostic into clinical practice could improve the personalisation of treatment for GC with PM and overcoming important drug resistance issues, enhancing the effectiveness of current therapy approaches.
Gesehen am 20.01.2026